Crises in Asia: Historical Perspectives and Implications - Kiseok Hong; Jong-Wha Lee; Hsiao Chink Tang (Asian Development Bank (ADB), 2009)
The paper analyzes the stylized features of historical crisis episodes for 21 developing Asian economies over 1961–2007. The paper finds that while there is substantial diversity, on average, recessions and financial downturns are more frequent, longer lasting, and more severe in Asia than in the Organisation for Economic Co-operation and Development countries. The paper also finds that the likelihood and severity of a recession tends to increase when it is associated with credit crunches or stock market crashes. Severe financial downturns or recessions in the global economy are often coupled with financial crises or recessions in Asia. In view of the current global crisis and severe financial downturns, Asian economies are expected to experience a severe recession in 2009.
hdl:11540/1809
Keywords: 330; Recession; Financial Crisis; Credit Crunch; Asia; Wirtschaftskrise; Wirtschaftsgeschichte; Asien